Proteomic analysis of the lymphocyte plasma membrane using cell surface biotinylation and solution-phase isoelectric focusing. - Peirce, M; Cope, A; Wait, R (2009)
Plasma membrane (PM) proteins are of particular interest to cell biologists because of their role in transducing information from the external environment to the cell interior, and because of their potential as therapeutic targets. The hydrophobicity and large size of these proteins renders their analysis by conventional proteomic approaches using 2D-electrophoresis problematic, limiting our ability to evaluate alterations of cell surface architecture as a function of varying physiological, pathological, or developmental state.In this chapter, we describe a simple method for enrichment and separation of plasma membrane proteins, prior to their identification by tandem mass spectrometry. Cell surface proteins are labeled with biotin using a reagent which does not enter the cell, purified by differential centrifugation and then affinity captured with streptavidin-agarose beads, before separation by a combination of solution-phase isoelectric focusing, and gradient gel electrophoresis, resulting in highly enriched membrane protein fractions suitable for characterization by mass spectrometry. We discuss the application of this protocol to the semiquantitative comparison of the plasma membrane proteins from resting and activated murine lymphocytes.